1995
DOI: 10.1093/gerona/50a.4.m203
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake and Mortality in the Frail Elderly

Abstract: Food intake is a strong predictor of survival even in moderately diseased elderly patients, suggesting possible low-cost interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…One important characteristic of this diet appears to be the high contribution of olive oil increasing the mono-unsaturated to saturated fat ratio even with a total fat intake of about 40% of total energy intake (Trichopoulou et al, 1995b). The one study that related macronutrient composition of the diet to survival revealed that decreasing protein and lipid intake were increasingly associated with mortality, while carbohydrate intake showed a threshold effect in frail elderly patients (Frisoni et al, 1995). The latter study points to the importance of suf®cient food intake.…”
Section: Differences Between Populationsmentioning
confidence: 99%
“…One important characteristic of this diet appears to be the high contribution of olive oil increasing the mono-unsaturated to saturated fat ratio even with a total fat intake of about 40% of total energy intake (Trichopoulou et al, 1995b). The one study that related macronutrient composition of the diet to survival revealed that decreasing protein and lipid intake were increasingly associated with mortality, while carbohydrate intake showed a threshold effect in frail elderly patients (Frisoni et al, 1995). The latter study points to the importance of suf®cient food intake.…”
Section: Differences Between Populationsmentioning
confidence: 99%
“…A good appetite is generally regarded as a sign of good health and a decreasing willingness or acceptance of food could be an early sign of the process of worsening health (Frisoni et al 1995). Since this process might be one of the indicators of frailty, attendance to this problem is of major importance.…”
mentioning
confidence: 99%
“…Other studies [3][4][5][6][7][8][9][10] have examined causes of weight change and its impact on morbidity and mortality in community dwelling as well as institutionalized older persons. No studies, however, have attempted to link patterns of weight change and feeding dysfunction with cause of death in a demented population.…”
mentioning
confidence: 99%